2020
DOI: 10.1002/jcp.29456
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from mesenchymal stem cells overexpressing MIF enhance myocardial repair

Abstract: Accumulating evidence has shown that mesenchymal stem cell (MSC)‐derived exosomes (exo) mediate cardiac repair following myocardial infarction (MI). Macrophage migration inhibitory factor (MIF), a proinflammatory cytokine, plays a critical role in regulating cell homeostasis. This study aimed to investigate the cardioprotective effects of exo secreted from bone marrow‐MSCs (BM‐MSCs) overexpressing MIF in a rat model of MI. MIF plasmid was transducted in BM‐MSCs. Exo were isolated from the supernatants of BM‐MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 41 publications
3
71
0
3
Order By: Relevance
“…Exosomes are important paracrine components, repairing tissue by encasing and sending RNAs and proteins (Phan et al, 2018;Shi et al, 2018). Previous study showed that exosomes from cardiac stem cells and mouse embryonic stem cells could afford the same cardioprotective effects as stem cells (Todorova et al, 2017;Liu et al, 2020). Nonetheless exosomes derive mainly from young donors and the contents of Aged-Exo cells may change and further reduce their reparative ability.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are important paracrine components, repairing tissue by encasing and sending RNAs and proteins (Phan et al, 2018;Shi et al, 2018). Previous study showed that exosomes from cardiac stem cells and mouse embryonic stem cells could afford the same cardioprotective effects as stem cells (Todorova et al, 2017;Liu et al, 2020). Nonetheless exosomes derive mainly from young donors and the contents of Aged-Exo cells may change and further reduce their reparative ability.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we found that the paracrine secretion effects of donor BM-MSCs were suppressed by hypoxic stimuli while were dramatically enhanced after irisin or FNDC5-MSCs treatment, suggesting that irisin or FNDC5 could play a cardioprotective role through paracrine secretion effects of BM-MSCs. Recently, exosomes from BM-MSCs have emerged as a potential strategy for MI (41,42) . Therefore, we further investigated the effects of FNDC5 on exosomes derived from BM-MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…MIF-2 in contrast to MIF appears to lack the necessary CXCR-interacting motifs necessary for activation, and it is believed to exert a more selective action in activating the tissue-protective CD74 signaling pathway. That said, MIF triggers the CD74/CD44/AMPK receptor signaling pathway, which promotes glucose uptake in cardiomyocytes and protects the heart during ischemia-reperfusion injury (93,94). Further studies are required to determine the potential of MIF/MIF-2 as a treatment strategy to protect the heart against ischemic injury.…”
Section: Cd74 Signaling In Protecting the Heart After Injurymentioning
confidence: 99%